College Students and SNAP: The New Face of Food Insecurity in the United States - Freudenberg, Nicholas (Am J Public Health, 2019)
Over the last decade, multiple studies of food insecurity among college students have found rates from 20% to more than 50%, considerably higher than the 12% rate for the entire US population. Reasons for higher rates of food insecurity among college students include a growing population of low-income college students, high college costs and insufficient financial aid, more financial hardship among many low- and moderate-income families, a weak labor market for part-time workers, declining per capita college resources, and Supplemental Nutritional Assistance Program (SNAP) policies that specifically exclude many college students from participation. This essay reviews the causes and consequences of food insecurity on campus, explores reasons for the low SNAP participation rate, and describes how campuses have responded to food insecurity. It summarizes federal, state, and local changes in SNAP policies that can facilitate college student participation and retention and suggests strategies for more robust and effective university responses to food insecurity, including SNAP enrollment campaigns, a stronger role for campus food services, and a redefinition of the goals and purposes of campus food pantries.